Effectiveness of Use of Electronic Module in Sociology Subjects of Social Change for Equality Education Package C - Hariyani, Mutia; Kusumawardani, Dwi; Sukardjo, Moch (Universitas Pendidikan Ganesha, 2021)
learning process is still conventional in the use of learning methods and media to affect student learning outcomes. With the use of electronic modules, abstract material can be concretized, making students interested and motivated in learning, and improving learning outcomes. The purpose of this study was to test the effectiveness of the electronic module on cognitive learning outcomes on social change material in the Package C Education program. The research approach used was quantitative. The type of research used is Pre-experimental. The design used in this research is One Group Pretest-Posttest. The research subjects were students of class XII package C program, totalling 38 students with details of 17 males and 21 females—data collection methods by observation, interviews, and tests. The instrument used is an objective test with a total of 10 items. The analysis of improving learning outcomes was analyzed using the N-Gain formula. The study results are based on N-gain analysis, and student learning outcomes show a value of 0.60 in the medium category, and the value of the effectiveness of N-gain in per cent is 60 with a moderately effective category. So that learning by using electronic modules can improve student learning outcomes.